2010
DOI: 10.1111/j.1440-1738.2010.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Parentage of low‐grade metasediments in the Sanbagawa belt, eastern Shikoku, Southwest Japan, and its geotectonic implications

Abstract: This study examines the geology of low‐grade (chlorite zone) metamorphic rocks in the Sanbagawa belt and of a Jurassic accretionary complex in the Northern Chichibu belt, eastern Shikoku, Japan. The bulk chemistries of metasandstones and metapelites in the Sanbagawa belt of eastern Shikoku are examined in order to determine their parentage. The Sanbagawa belt can be divided into northern and southern parts based on lithology and geologic structure. Geochemical data indicate that metasediments in the northern a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
9
1
Order By: Relevance
“…113-88) of the Shimanto accredionary wedge, respectively, which suggests that the Minawa protoliths were formed during an extended period of time. Otoh et al (2010) found zircons dated at 88 ± 10 and 91 ± 9 Ma at the base of the Minawa Formation in roughly the same area thus confirming the general conclusions of Kiminami (2010). Late Cretaceous Sanbagawa metamorphics also occur in the Kii Peninsular (Otoh et al, 2010), the Chubu part of the Sanbagawa Metamorphic Belt (Tsutsumi et al, 2012), in Kyushu (parts of the Nagasaki Metamorphics, Kouchi et al, 2011) and in north-western Shikoku (this study).…”
Section: Sanbagawa Metamorphic Rocks Vs Shimanto Metamorphic Rockssupporting
confidence: 85%
See 2 more Smart Citations
“…113-88) of the Shimanto accredionary wedge, respectively, which suggests that the Minawa protoliths were formed during an extended period of time. Otoh et al (2010) found zircons dated at 88 ± 10 and 91 ± 9 Ma at the base of the Minawa Formation in roughly the same area thus confirming the general conclusions of Kiminami (2010). Late Cretaceous Sanbagawa metamorphics also occur in the Kii Peninsular (Otoh et al, 2010), the Chubu part of the Sanbagawa Metamorphic Belt (Tsutsumi et al, 2012), in Kyushu (parts of the Nagasaki Metamorphics, Kouchi et al, 2011) and in north-western Shikoku (this study).…”
Section: Sanbagawa Metamorphic Rocks Vs Shimanto Metamorphic Rockssupporting
confidence: 85%
“…It is recognized that not all Sanbagawa metamorphics have the same protolith age (Tsutsumi et al, 2009;Kiminami, 2010;Tsutsumi et al, 2012) and thus, we suggest to refer to the various units as 'Jurassic Sanbagawa Belt' and 'Early' and 'Late Cretaceous Sanbagawa Belt', respectively. Likewise, the available age data suggest that the Sanbagawa metamorphics have been subjected to metamorphism during a period of time and not at a specific point in time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whole‐rock major element compositions of quartz eclogites and mafic clots from the Gongen area and other lithologies of the Sanbagawa metamorphic belt. Data sources are as follows: Quartz eclogite and mafic clot (Miyamoto et al, ; Utsunomiya et al, ; Yokoyama, unpublished data; this study), metabasalt and metagabbro (Aoya et al, ; Banno, ; Endo et al, ; Ernst, Seki, Onuki, & Gilbert, ; Goto & Banno, ; Nozaki et al, ; Okamoto et al, ; Utsunomiya et al, ; Weller, Wallis, Aoya, & Nagaya, ; Enami, Iwata, and Yokoyama, unpublished data), metasediments (Aoya et al, ; Banno, ; Ernst et al, ; Fujiwara, Yamamoto, & Mimura, ; Goto et al, ; Kiminami, ; Kiminami & Ishihama, ; Kiminami & Toda, ; Utsunomiya et al, ; Zaw Win Ko et al, ; Enami, unpublished data) of the Sanbagawa metamorphic belt. Mfc, mafic clot; Qpd, quartz‐poor domain; Qrd, quartz‐rich domain in quartz eclogite (GE1501a) shown in Figure .…”
Section: Chemical Compositions Of Quartz Eclogitementioning
confidence: 94%
“…Whole‐rock minor element compositions of quartz eclogites and mafic clots from the Gongen area and other lithologies of Sanbagawa metamorphic belt in (a) Ti/50‐Zr‐Sr/2 and (b) V–Ba diagrams. Data sources are as follows: Quartz eclogite and mafic clot (Miyamoto, Enami, Tsuboi, & Yokoyama, ; Utsunomiya, Jahn, Okamoto, Ota, & Shinjoe, ; this study), metabasalt and metagabbro (Aoya, Tsuboi, & Wallis, ; Endo, Wallis, Tsuboi, Aoya, & Uehara, ; Nozaki, Nakamura, Awaji, & Kato, ; Okamoto, Maruyama, & Isozaki, ; Uno et al, ; Utsunomiya et al, ; Enami, unpublished data), metasediments (Aoya et al, ; Goto, Higashino, & Sakai, ; Kiminami, ; Kiminami & Ishihama, ; Kiminami & Toda, ; Utsunomiya et al, ; Enami, unpublished data). Mfc, mafic clot; Qpd, quartz‐poor domain; Qrd, quartz‐rich domain in quartz eclogite (GE1501a) shown in Figure .…”
Section: Chemical Compositions Of Quartz Eclogitementioning
confidence: 99%